Barries to upscale EV charging station infrastructure in Thailand - Suthida Chaiyaratsamee; Shobhakar Dhakal; Weerakorn Ongsakul; Badir, Yuosre; PEA-AIT Education Cooperation Project; Royal Thai Government Fellowship (Pathum Thani, Thailand : Asian Institute of Technology, 2018)
Nowadays, the world is facing several environmental issues such as air pollution, greenhouse gas emissions, and energy security. Electric vehicles (EVs) are one resolution that can solve these issues. Due to EVs are powered by electricity, thereby reducing C02 emissions, decreasing dependence on fossil fuel consumption. Although EV s have many benefits, there is still having several obstacles that hinder the widespread use of EVs. The one of major barrier is scarcity of EV charging infrastructure. A scarcity of EV charging station can affect EV s user confidence. Even though most of EV s users can recharge their vehicle at home but they are also concerned about the limited driving range for long distance. Therefore, if the shortage of EV charging station can be solved, it will make the use of EV s rising. In Thailand, EV s have become known and are already used according to Thai government has launched the energy efficiency plan, policy and measure to encourage the use of EV s. However, the use of EV s in Thailand stills not much because it is in the first stage of the plan. There are many barriers that impede the use of EV s in Thailand such as high price of EV s, lack of knowledge, and lack of EV charging station. This research will study the barriers to upscale EV charging station infrastructure in Thailand by using the qualitative methodology, in-depth interview and prioritize barriers, respectively. This research aims to find answers by in-depth interview from the people perspective which work involved in the EV charging station. The results expected are aware of the actual barriers which affect to upscale EV charging station infrastructure in Thailand. Moreover, the result can also be deployed to develop a charging station in the future.
A research studysubmitted in partial fulfillment of the requirements for the degree of Master of Business Administration in Energy Business Management, School of Environment, Resources and Development
Keywords: Electric vehicles -- Thailand; Battery charging stations (Electric vehicles) -- Thailand